Perceptions of prognosis and goal of treatment in patients with malignant gliomas and their caregivers. Issue 5 (17th April 2020) - Forst, Deborah A; Quain, Kit; Landay, Sophia L; Anand, Maya; Kaslow-Zieve, Emilia; Mesa, Michelle M; Jacobs, Jamie M; Dietrich, Jorg; Parsons, Michael W; Horick, Nora; Greer, Joseph A; Batchelor, Tracy T; et al.
Abstract: Background: Patients with malignant gliomas have a poor prognosis. However, little is known about patients' and caregivers' understanding of the prognosis and the primary treatment goal. Methods: We conducted a prospective study in patients with newly diagnosed malignant gliomas (N = 72) and their caregivers (N = 55). At 12 weeks after diagnosis, we administered the Prognosis and Treatment Perceptions Questionnaire to assess understanding of prognosis and the Hospital Anxiety and Depression Scale to evaluate mood. We used multivariable regression analyses to explore associations between prognostic understanding and mood and McNemar tests to compare prognostic perceptions among patient-caregiver dyads (N = 48). Results: A total of 87.1% (61/70) of patients and 79.6% (43/54) of caregivers reported that it was "very" or "extremely" important to know about the patient's prognosis. The majority of patients (72.7%, [48/66]) reported that their cancer was curable. Patients who reported that their illness was incurable had greater depressive symptoms (B = 3.01, 95% CI, 0.89-5.14, P = .01). There was no association between caregivers' prognostic understanding and mood. Among patient-caregiver dyads, patients were more likely than caregivers to report that their primary treatment goal was cure (43.8% [21/48] vs 25.0% [12/48], P = .04) and that the oncologist's primary goal was cure (29.2% [14/48] vs 8.3% [4/48], P = .02). Conclusions: Patients with malignant gliomas frequently hold inaccurate perceptions of the prognosis and treatment goal. Although caregivers more often report an accurate assessment of these metrics, many still report an overly optimistic perception of prognosis. Interventions are needed to enhance prognostic communication and to help patients cope with the associated distress.